2017
DOI: 10.1002/nbm.3770
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of lithium distribution in the rat brain ex vivo using lithium‐7 magnetic resonance spectroscopy and imaging at 17.2 T

Abstract: Lithium is the first-line mood stabilizer for the treatment of patients with bipolar disorder. However, its mechanisms of action and transport across the blood-brain barrier remain poorly understood. The contribution of lithium-7 magnetic resonance imaging ( Li MRI) to investigate brain lithium distribution remains limited because of the modest sensitivity of the lithium nucleus and the expected low brain concentrations in humans and animal models. Therefore, we decided to image lithium distribution in the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Rodent MRSI studies have also reported regional variation in 7 Li signal intensity across the brain in vivo,36, 37 but to achieve adequate resolution, scan duration is often several hours such that pharmacokinetic factors must be considered when interpreting signal intensity 3840. A recent ultra-high field strength, ex vivo 7 Li-MRI study of the rat brain also reported signal heterogeneity as well an overall correlation between signal intensity and mass spectroscopy derived lithium concentrations across brain regions 41. We observed heterogeneity in lithium distribution in all subjects, but visually different distributions between subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Rodent MRSI studies have also reported regional variation in 7 Li signal intensity across the brain in vivo,36, 37 but to achieve adequate resolution, scan duration is often several hours such that pharmacokinetic factors must be considered when interpreting signal intensity 3840. A recent ultra-high field strength, ex vivo 7 Li-MRI study of the rat brain also reported signal heterogeneity as well an overall correlation between signal intensity and mass spectroscopy derived lithium concentrations across brain regions 41. We observed heterogeneity in lithium distribution in all subjects, but visually different distributions between subjects.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate [Li] from the intensity of our 7 Li images, we adopted a modified phantom replacement approach that we validated in a previous ex vivo 7 Li MRI study of rats pretreated with Li (29). The same 7 Li MRI protocol was used to acquire at room temperature an image from a 7-L cylindrical phantom of Li chloride (50 mmol/L, pH = 7.0).…”
Section: Lithium Concentration Quantificationmentioning
confidence: 99%
“…However, the spatial resolution and precision of those images remain limited by the low [Li] at therapeutic range (0.3-1.0 mmol/L in the plasma). Even so, those 7 Li-NMR studies have made important observations about Li compartmentation and its cerebral distribution (21,23,25,27,29). Yet so far, those studies have failed to identify regions of the brain where Li would accumulate significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1994) used 6 Li(n. ) 3 H nuclear reaction in the presence of a dielectric a particle track detector to image lithium in adult rat brain, but the resolution was poor. Lithium-7 nuclear magnetic resonance ( 7 Li-NMR, 23. Stout et al, 2017) and 3D 7 Li magnetic resonance (62.…”
Section: Entry and Distribution Of Lithium In Developing Brainmentioning
confidence: 99%